Peran Guru BK dalam Membantu Penyesuaian Diri Santri Baru di Pondok Pesantren - Feby Novianti; Desi Erawati; Arini Safitri (Jurnal Bimbingan dan Konseling Ar-Rahman, 2023)
Independence in new students is a fundamental thing that must be possessed by students in order to support a better pesantren life. The role of counseling teachers is one of the supports for new students in achieving independence, whether or not there is a role of counseling teachers in supporting the independence of students. The purpose of this study is to determine whether or not the role of counseling teachers in helping new students to make self-adjustment to achieve independence. This study uses a descriptive qualitative research approach with the primary data source is a counseling teacher with a S.Ag graduate, who has been working at MA for three years. As the initial data is the 10th grade students both science and language totaling 10 students, then in collecting research data through observation, interviews and documentation. Through the results of the research conducted, the role of counseling teachers for new students in increasing independence can be said that there is no program developed related to the independence of new students. The guidance or services provided are still limited to general services provided to all new students related to the introduction of the school environment and the boarding school itself. In further research, a study can be conducted on how much influence the counseling teacher has in helping new students adapt to the new environment._____________________________________________________________Kemandirian pada santri baru merupakan hal mendasar yang harus dimiliki oleh para santri demi menunjang kehidupan pesantren yang lebih baik. Peranan guru BK menjadi salah satu penunjang untuk santri baru dalam mencapai kemandirian, ada tidaknya peranan guru BK dalam menunjang kemandirian santri. Tujuan penelitian ini untuk mengetahui ada tidaknya peranan guru BK dalam membantu para santri baru untuk melakukan penyesuaian diri untuk mencapai kemandirian. Kajian ini menggunakan pendekatan penelitian kualitatif deskriptif dengan sumber data primer adalah guru BK dengan lulusan S.Ag, telah tiga tahun lamanya bekerja di MA. Sebagai data awal adalah para santri kelas 10 baik Ipa dan Bahasa berjumlah 10 santri, selanjutnya dalam pengumpulan data penelitian melalui observasi, wawancara dan dokumentasi. Melalui hasil penelitian yang dilakukan, peranan guru BK untuk santri baru dalam meningkatkan kemandirian dapat dikatakan belum ada program yang dikembangkan terkait kemandirian santri baru. Bimbingan atau layanan yang diberikan masih sebatas layanan umum diberikan seluruh santri baru terkait pengenalan lingkungan sekolah serta pondok pesantren itu sendiri. Dalam penelitian selanjutnya dapat dilakukan sebuah penelitian mengenai seberapa besar pengaruh guru BK dalam membantu para santri baru dalam beradaptasi dengan lingkungan baru.